Testing generalized second law of thermodynamics in cosmological models with bulk viscosity and modified gravity - Khandro K. Chokyi; Surajit Chattopadhyay (European Physical Journal C: Particles and Fields)
Abstract This study examines the validity of the Generalized Second Law of Thermodynamics (GSLT) to generalized Chaplygin gas (GCG) and modified Chaplygin gas (MCG) models within the general relativity(GR) framework and modified gravity framework namely the f(T) gravity. Three distinct models of GCG and MCG are analyzed with bulk viscosity included in the GR framework to account for the dissipative process during cosmic evolution while the f(T) gravity is considered without bulk viscosity. To study the thermodynamic implications of the model, our study employs three distinct forms of entropy: Tsallis, Barrow and Sharma–Mittal entropy. Furthermore, a highly generalized version of holographic cutoff has also been explored under the purview of the reconstruction approaches under consideration inspired by The European Physical Journal C, 77:1–8. Our results confirm that the models satisfy the GSLT with total entropy change remaining positive thus confirming the thermodynamic stability of GCG and MCG and the robustness of these forms of entropy in describing the universe’s thermodynamic behaviour. Additionally, for the two Chaplygin gas models with bulk viscosity in the GR framework, the GSLT is validated and the results show the thermodynamical stability of these models with the inclusion of bulk viscosity term and interaction terms as well.